ปัจจัยที่มีผลต่อการตัดสินใจในห่วงโซ่อุปทานตำราเรียนของอาจารย์ในมหาวิทยาลัยเชียงใหม่ - มัลลิกา ริมสกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This study on the factors affecting faculty members’ decision making in the textbook supply chain, the case of Chiang Mai University, has two objectives: 1) to understand the factors determining the decision of faculty members of Chiang Mai University to produce textbooks, and 2) to probe into the process to publish technical papers/textbooks written by CMU faculty members. The information for the present investigation was collected from 165 samples of CMU faculty members. Both descriptive and quantitative methods were used for the analysis particularly the application of logistic regression technique for analysis of factors affecting faculty members’ decision in the past, at present, and in the future to produce textbooks. From the information on general personal background, it was found that the majority of questionnaire respondents were characterized as female, 41 – 50 years old, with the highest educational attainment at doctorate degree level, and in most cases holding the academic position as lecturer followed by assistant professor. Most samples under study revealed, up to the present, they had not yet produced any textbook. However, in the future, their likelihood to produce textbooks would be greater than otherwise. From the investigation on the marginal gain in terms of academic benefit from textbook production, the CMU faculty members appeared to place primary importance on the advancement in their knowledge and scholastic capability. Meanwhile, the examination on the marginal cost of textbook production venture revealed that the faculty members gave very high consideration to the factors of textbook preparation, textbook production, and market distribution. To answer the second objective of the present study, an interview was made with personnel of Chiang Mai University Press regarding the publication of textbooks and technical papers written by CMU faculty members. It was found that there were three main factors giving rise to problems and obstacles in the preparation to produce textbooks including 1) the personal factor on the part of faculty members themselves, 2) the factor of economic return, and 3) the factor concerning the presentation of pictures and other illustrations in the textbooks. Generally, Chiang Mai University Press has confronted no problem in the process of producing textbooks written by CMU faculty members as clear rules and regulations have been established on the procedures for the preparation and production of technical papers/textbooks. Individual faculty member can get the printing shop or printing house to lay out the printing format for the book and make adjustment appropriately as required by the author. In the aspect of market distribution, Chiang Mai University Press considered the textbook market was quite narrow giving rise to a rather stable sale volume. This is due to its inability to open new market which is in turn consequential to its limited function as an organ of Chiang Mai University. Thus, Chiang Mai University Press so far has been operated not so much for business interest but mostly for the publication of outputs of CMU faculty members rather than for profit.